2005
DOI: 10.1136/bmj.331.7531.1512
|View full text |Cite
|
Sign up to set email alerts
|

Shape of glass and amount of alcohol poured: comparative study of effect of practice and concentration

Abstract: Objective To determine whether people pour different amounts into short, wide glasses than into tall, slender ones. Design College students practised pouring alcohol into a standard glass before pouring into larger glasses; bartenders poured alcohol for four mixed drinks either with no instructions or after being told to take their time. Setting University town and large city, United States. Participants 198 college students and 86 bartenders. Main outcome measures Volume of alcohol poured into short, wide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 11 publications
6
99
3
1
Order By: Relevance
“…Consumption behaviours can change with the shape of the glass [4,5], the size of the plateware [6][7][8], and the size of the cutlery with which a person eats [9,10]. Consumption behaviours are also affected by what a person hears (see [11] for a review) as well as by ambient lighting and music [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Consumption behaviours can change with the shape of the glass [4,5], the size of the plateware [6][7][8], and the size of the cutlery with which a person eats [9,10]. Consumption behaviours are also affected by what a person hears (see [11] for a review) as well as by ambient lighting and music [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in two studies, both adults and children underestimated the amount of liquid in short and wide glasses (24,25). In addition, people cannot accurately estimate the calories in various food items and underestimate calories depending on the context in which the foods are presented (26).…”
Section: Inability To Judge Volume or Calories Either Through Visual mentioning
confidence: 99%
“…Some studies have shown respondents pictures of containers and glasses with pour levels marked with letters rather than volume labels and asked them to find the closest matching vessel and pour level, or in faceto-face situations, to solicit responses using actual glassware with labeled pour levels [153]. Other strategies include having respondents pour a drink like their usual one into glasses provided to estimate their usual pour [162,163] or to have them attempt to pour a standard drink into provided glasses to gauge their ability to do so [164,165]. Finally, direct measurement of simulated usual drinks poured at home is the method that we believe is most accurate for use in any survey mode where respondents are contacted in their own home (and a large proportion of drinking is in home settings-not always the case).…”
Section: Home Drink Measurement Strategiesmentioning
confidence: 99%